The Intensity of MSME Actors in Pontianak Adopting Digital Financial Services (Fintech) in Improving Sustainable Financial Literacy - Fry Melda Saragih; Melyanto Melyanto (Universitas Hamzanwadi, 2025)
The rapid penetration of technological developments has changed the landscape of Indonesia's economy towards a digital economy and financial technology (fintech), including Micro, Small and Medium Enterprises (MSMEs) which continue to face classic problems such as funding, digital marketing, and even financial management that hinder business growth. This study aims to identify the factors influencing the intention of MSMEs to adopt fintech services in Pontianak, West Kalimantan. The research design uses a quantitative approach where data was distributed through questionnaires to 245 MSME traders and analyzed using the Smart PLS-SEM (Partial Least Square-Structural Equation Modeling) model by combining two well-known theories in predicting individual behavior and technology acceptance, namely the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB). The results show that Perceived Ease of Use (PEOU) and Perceived Usefulness (PU) have a significant effect on Attitude Toward Behavior (ATB). Similarly, Perceived Ease of Use (PEOU) and Attitude Toward Behavior (ATB) influence Behavioral Intention (BI). Conversely, Perceived Usefulness (PU), Trust (T), and Social Influence (SI) did not significantly influence Behavioral Intention (BI). This study implies the need for collaboration between regulators (OJK) and all stakeholders, including MSMEs, to improve financial literacy by continuing to educate them about fintech products and services. The hope is that MSMEs can integrate with fintech not only in financing but also in scaling up their businesses, finances, human resources, and other areas.